PSV-6 Effects of chilled drinking water and cooled floor pads on behavior of lactating sows under heat stress. (30th November 2020) - Li, Yuzhi; Zhu, Yunhui; Reese, Michael; Buchanan, Eric; Johnston, Lee
Abstract: This study was conducted to evaluate effects of chilled drinking water and cooled floor pads on behavior of lactating sows under heat stress. Sows were housed in individual farrowing stalls in two rooms with temperatures being controlled at 29.4°C (0700h to 1900h) and 23.9°C (1900h to 0700h). Sows in one room (treatment), but not in the other room (control) were provided with chilled drinking water (13 to 15°C) and cooled floor pads (15 to 18°C). Behavior of sows (n=15 sows/treatment; parity=1 to 6) was video recorded during farrowing, and d 1, 3, 7, 14, and 21 after farrowing. Videos were viewed to register birth time of each piglet. Number of drinking bouts and duration of each bout were registered for 2 h (1530h to 1730h) each day after farrowing. Postures (lying laterally, lying ventrally, sitting, and standing) were recorded by scanning video-recordings at 5-min intervals for 24 h each day after farrowing, and time budget for each posture was calculated. Data were analyzed using the Glimmix Procedure of SAS. No effect of treatment was detected for litter size born, farrowing duration, or birth interval (P >0.33; Table 1). Neither frequency nor duration of drinking bouts was affected by treatment (P >0.27). No significant difference was observed in time budget for each posture (P >0.46) between treatment and control groups. As lactation progressed, sows increased drinking frequency (from 1.2 drinks/2h on d 1 to 4.9 drinks/2h on d 21; P< 0.001) and time spent lying ventrally (8% to 14%; P< 0.0001), standing (4% to 10%; P< 0.001), and sitting (2% to 4%; P< 0.0001), and decreased time spent lying laterally (86% to 67%; P< 0.0001) in both control and treatment rooms. These results indicate that chilled drinking water and cooled floor pads did not affect behavior of sows during farrowing and lactation in the current study.